Best Practices for Smoking Cessation Interventions in Primary Care. Issue 4 (2009) - McIvor, Andrew; Kayser, John; Assaad, Jean-Marc; Brosky, Gerald; Demarest, Penny; Desmarais, Philippe; Hampson, Christine; Khara, Milan; Pathammavong, Ratsamy; Weinberg, Robert
Abstract : BACKGROUND: In Canada, smoking is the leading preventable cause of premature death. Family physicians and nurse practitioners are uniquely positioned to initiate smoking cessation. Because smoking is a chronic addiction, repeated, opportunity-based interventions are most effective in addressing physical dependence and modifying deeply ingrained patterns of beliefs and behaviour. However, only a small minority of family physicians provide thorough smoking cessation counselling and less than one-half offer adjunct support to patients. OBJECTIVE: To identify the key steps family physicians and nurse practitioners can take to strengthen effective smoking cessation interventions for their patients. METHODS: A multidisciplinary panel of health care practitioners involved with smoking cessation from across Canada was convened to discuss best practices derived from international guidelines, including those from the United States, Europe, and Australia, and other relevant literature. The panellists subsequently refined their findings in the form of the present article. RESULTS: The present paper outlines best practices for brief and effective counselling for, and treatment of, tobacco addiction. By adopting a simple series of questions, taking 30 s to 3 min to complete, health care professionals can initiate smoking cessation interventions. Integrating these strategies into daily practice provides opportunities to significantly improve the quality and duration of patients' lives. CONCLUSION: Tobacco addiction is the most important preventable cause of morbidity and mortality in Canada. Family physicians, nurse practitioners and other front-line health care professionals are well positioned to influence and assist their patients in quitting, thereby reducing the burden on both personal health and the public health care system.